PENGUKURAN DIMENSI LUAR, DALAM SERTA TEBAL RELATIF DIVAIS ELEKTRONIK MEMORI USB MENGGUNAKAN CITRA RADIOGRAFI - Ade Agung Harnawan; Prihatin Oktivasari (Lambung Mangkurat University Press, 2013)
ABSTRACT: Radiographic imaging has been done for profile aluminium witharrange in steps and 5 USB memory to measure the dimension inner and outerpart of 5 USB memory without destroying it. Based on this image, the functionof characterization for relative thickness of aluminium's profile with grayscalelevel is gained. With characteristic mentioned before the dimension and relativethickness of profile memory USB is determined. The result are the dimensionouter part of profile that consist of the length is 31–57 pixel, the width is 13–22pixel and the wide is 465–1197 pixel2, later the dimension inner part of profilethat consist of the length is 28–30 pixel, the width is 10–16 pixel and the wide is300–480 pixel2 and the last, the relative thickness of electronics device is rangefrom 3,36–7,62 mm.Keywords: radiographic imaging, dimension of USB memory, relativethickness, aluminium